Artificial trees for atmospheric carbon capture-a review - VENKATARAGHAVAN.R; ARVIND PRABHU.T; IVO ROMAULD S; BRINDHA DEVI P (International Journal of Pharma and Bio Sciences, 2017)
Carbon emission is the major cause for global warming; Scientists have been working to reduce the carbon emissions ever since the effects were identified. There are number of methods to reduce the excess carbon dioxide that are present in the atmosphere, in this work, we have suggested a way to reduce the atmospheric carbon dioxide by a technology which will manifest in the form of “Artificial trees”. The artificial trees are thousand times more effective in carbon capture than aerobic tress anddoes not release the absorbed carbon back again into the environment. The carbon capture by the trees is accomplished by special leaves that are coated with suitable sorbent. The absorbed carbon dioxide from these artificial trees could be utilized or converted into useful forms hydrocarbons-sources of fuel or buried underground. Therefore, in this review we discuss the various techniques of carbon capture and sequestration.